Land Use and Property Market Impacts of the Relocation of Athens International Airport - Alexis Politakis (European Regional Science Association (ERSA), 2006)
This paper investigates the impact of the relocation of Athens International Airport (AIA), one of the most significant urban developments in the modern history of the city of Athens, on land uses and the property market around the former airport site (FAS) and the new Eleftherios Venizelos airport (EV). Airport relocations are in themselves relatively rare events. In this dissertation, for the first time, sources from various fields are brought together to bear on this relocation case. Finally, this study highlights the opportunities being missed in development and planning terms, as a result of chronic weaknesses of the Greek planning system.
Keywords: 330